Elements of marketing innovation and its impact on marketing performance/ exploratory study on a sample of individuals working a number of commercial companies in the city of Zakho - Omar, Mohammed Abd (Humanities Journal of University of Zakho, 2018)
The objective of the research was to determine the relationship between the elements of marketing innovation and the marketing performance of a group of commercial companies operating in Zakho city. The research method used descriptive analytical method to test a sample of (60) members of commercial companies and employees in companies. Statistical analysis and presentation of the statistical (SPSS-20) using statistical percentages, averages, standard deviations, correlation and effect relationships. The results of descriptive analysis of the main variable, elements of marketing innovation, showed that (72.78%). Based on the hypothesis of the research hypotheses and the results received, the research reached (the existence of a significant correlation between the elements of marketing innovation and marketing performance) And to (the existence of a significant effect relationship to the elements of marketing innovation and marketing performance). The research found a number of conclusions. The most important of these were the attempts by commercial companies to adopt innovation in the market and the view that marketing innovation is better than technological innovation in developing their products in order to achieve the best performance. The research also recommends finding some kind of common interest The company and the interests of customers by taking into consideration the income of customers when pricing their products and advanced methods of pricing when providing products with the need to maintain a high level of quality and that lead to a high customer loyalty..